The study of the chemistry of tinospora crispa (Menispermaceae) - Serini, Juan (Universiti Malaysia Sarawak, UNIMAS, 2009)
Tinospora crispais the climbing, thorny plants that included in the family Menispermaceae. The present study was done on the crude extract of the stem o f this plant; crude hexane, crude DCM, crude EtOAc, crude MeOH. Analytical TLC and cytotoxicity test was carried out on each crude extracts, followed by fractionation using CC and monitored by using analytical TLC. Selected components were further analyzed by using NMR spectrometer and FTIR spectrometer for functional groups analysis.